STUDENT PERCEPTIONS OF MAJOR HEALTH NEEDS OF ADULT REFUGEES FROM UKRAINE - Makanangot, Neha Nuhman (My University, 2024)
Perceptions of Major Health Needs of Adult Refugees from Ukraine Neha Makanangot Mentor: Larson, Kim L Purpose: This study aimed to examine the perceptions of the health needs of war-affected adult refugees from Ukraine. Significance: Ukrainian refugees affected by war confront formidable obstacles when attempting to access essential healthcare services and effectively manage chronic health conditions, including cardiac problems and cancer. These challenges are exacerbated by the upheaval caused by displacement, forcing individuals to navigate unfamiliar healthcare systems in their host countries. Moreover, the resources available for healthcare in these settings are often constrained, further impeding refugees' ability to receive timely and comprehensive medical care. Understanding the healthcare needs of this vulnerable population is imperative to prevent potential health crises and ensure the provision of culturally competent care by nurses and healthcare workers in the future. Methodology: This qualitative descriptive study, conducted as part of a larger mixed-methods research project titled "Intercultural Nursing Care for the Health and Well-being of Ukrainian Refugees." Nursing students from ECU (n=7) and JU (n=11) in Poland met in synchronous class sessions for a Global Health International Virtual Exchange course. Students submitted reflection papers after each of five class sessions, these reflections (180 pages) generated data for this study. Data management included creation of 18 transcripts and a codebook. Analytic techniques included data matrices, content and thematic analysis. Results: The study identified three primary categories: vaccine-related issues, a compromised healthcare system, and the burden of disease. Vaccine-related issues included concerns like vaccine delays, mandatory vaccines, hesitancy, and the anti-vaccination movement. The weakened healthcare system encompassed challenges such as limited access to free health insurance, inefficiencies in the Polish healthcare system, and a nursing shortage. Lastly, the burden of disease highlighted preventable, communicable, and chronic illnesses affecting Ukrainian adults. Discussion: The study's findings highlight the multifaceted challenges facing the health of Ukrainian refugees. Vaccine-related issues reveal barriers hindering immunization acceptance, while the recognition of a compromised healthcare system emphasizes systemic deficiencies in healthcare delivery. Additionally, the burden of disease highlights the urgent need for comprehensive healthcare interventions. These results emphasize the importance of implementing targeted strategies to address healthcare access barriers, improve vaccination rates, and alleviate the impact of preventable diseases on the well-being of Ukrainian refugees.
Keywords: Ukraine, Refugee, Adult Health